2013
DOI: 10.5414/cn107673
|View full text |Cite
|
Sign up to set email alerts
|

High-dose intravenous epoetin does not increase blood pressure in critically ill patients with acute kidney injury

Abstract: We concluded that intravenous high dose epoetin does not acutely increase blood pressure, suggesting no acute vasoconstrictor effect in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Most previous NEE formulas used 1/100 or 1/150 as the conversion ratio for dopamine [12,15,16,20,23]. Two randomized trials showed that approximately 80 and 140 times the dose of dopamine was required to reach the same MAP target when compared with norepinephrine, respectively [31,32].…”
Section: Proposed Updated Norepinephrine Equivalent Scorementioning
confidence: 99%
See 1 more Smart Citation
“…Most previous NEE formulas used 1/100 or 1/150 as the conversion ratio for dopamine [12,15,16,20,23]. Two randomized trials showed that approximately 80 and 140 times the dose of dopamine was required to reach the same MAP target when compared with norepinephrine, respectively [31,32].…”
Section: Proposed Updated Norepinephrine Equivalent Scorementioning
confidence: 99%
“…However, the major issue with NEE is that there is no standardized method for measuring the potency of vasopressors. As a result, there are several different calculation formulas for NEE [12,13,15,16,[20][21][22][23]. Inconsistent calculation methods for NEE will make it difficult to compare or interpret the results between clinical studies.…”
Section: Introductionmentioning
confidence: 99%